The impact of stress on elite volleyball players female and male in Albania - Pogoni, Artan; Bajaziti, Artemis; Lleshi, Enkeleida (Edelweiss Applied Science and Technology, 2025)
Aims to examine the relationship between stress and the social environment for elite Albanian volleyball players. The impact of stress is individual and subjective. Methods: In total, there are 14 elite volleyball teams that participate in the National Championship in Albania. There are 7 female teams (no. 105) and 7 male teams (no. 102) competing in the National Championship in Albania over the age of 18. The number of selected subjects is a statistically representative sample of the target group, calculated with a confidence coefficient of over 92%. The applied scientific instrument is the standardized Athlete Psychological Strain Questionnaire (APSQ). The questionnaire contains 30 statements, 6 for each stress dimension. For each statement, the athletes expressed their responses on a scale from 1 to 5. Results: All the project results were statistically documented; IBM SPSS Statistics 26 and Microsoft Excel statistics were used. The level of significance was set at p < 0.05. Only in dimension 3 (stress from pressure outside of sports) do volleyball players experience a common point where females show 44.71% and males 44.85%. Conclusions: The lack of significant differences between men and women indicates that gender does not determine psychological stress states in athletes.